p53 Affects PGC1α Stability Through AKT/GSK-3β to Enhance Cisplatin Sensitivity in Non-Small Cell Lung Cancer - Deng, Xinyue; Li, Yang; Gu, Shuang; Chen, Yingying; Yu, Bingbing; Su, Jing; Sun, Liankun; Liu, Yanan (Frontiers in Oncology, 2020)
Drug resistance greatly limits the therapeutic efficacy of treatment of non-small cell lung cancer (NSCLC). One of the important factors is the dysfunction of tumor suppressor p53. Recent studies have suggested that p53 suppresses tumors by regulating number of mitochondrial proteins, including peroxisome proliferator-activated receptor coactivator (PGC1α). Although several studies have confirmed the interaction between p53 and PGC1α, the precise mechanism has not been completely determined in NSCLC. In this study, we investigated the specific signaling between p53 and PGC1α to improve anti-tumor drug effects on NSCLC. We found that low expression of p53 and high expression of PGC1α correlated with shorter survival time of NSCLC patients. In vitro experiments confirmed that NCI-H1299 (p53-null) cells had high levels of PGC1α and were insensitive to cisplatin (CDDP). When PGC1α was knocked down, the sensitivity to cisplatin was increased. Notably, the stability of PGC1α is an important mechanism in its activity regulation. We demonstrated that p53 decreased the stability of PGC1α via the ubiquitin proteasome pathway, which was mediated by protein kinase B (AKT) inhibition and glycogen synthase kinase (GSK-3β) activation. Therefore, p53 may regulate the stability of PGC1α through the AKT/GSK-3β pathway, thus affect the chemosensitivity of NSCLC.